Nova ureditev potrošnikovih pravic v primeru dobave digitalnih vsebin in storitev - Renko, Jernej (Pravni letopis, 2022)
Directive (EU) 2019/770 on the supply of digital content and services introduces a new specific regime of consumer rights in the area of consumer contract law where the subjectmatter of a contract between a trader and a consumer constitutes digital content or services. Consumers who provide personal data to a trader in exchange for digital content or services have equal contract rights as those who pay the purchase price in cash. This article focuses on a comprehensive presentation of the scope of Directive (EU) 2019/770 and of individual consumer rights with regard to supply, conformity requirements for digital content and services, contracutal remedies and other rights, and highlights some advantages and disadvantages of the newly adopted regime. The author, relying on the German implementation of Directive (EU) 2019/770 in the German BGB, suggests some approaches that could also be used by the Slovenian legislator when implementing the Directive in the amendment to the Consumer Protection Act.
Keywords: digitalne storitve; osebni podatki; pogodbeno pravo; potrošniško pogodbeno pravo; potrošništvo; pravice potrošnikov; Zakon o varstvu potrošnikov